The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsinfecdis.3c00106
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Binding to Terminal Sialic Acid of Gangliosides Embedded in Lipid Membranes

Abstract: Multiple recent reports indicate that the S protein of SARS-CoV-2 specifically interacts with membrane receptors and attachment factors other than ACE2. They likely have an active role in cellular attachment and entry of the virus. In this article, we examined the binding of SARS-CoV-2 particles to gangliosides embedded in supported lipid bilayers (SLBs), mimicking the cell membrane-like environment. We show that the virus specifically binds to sialylated (sialic acid (SIA)) gangliosides, i.e., GD1a, GM3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…This labelling approach for enveloped viruses has been applied by multiple groups including us. [11,12,15,39,41] We characterized the labelled viruses upon fluorescence imaging with wide-field illumination and compared the signal intensity using a control system (liposomes labelled with DiI). The particle intensity analysis reveals that < 20 % of the labelled viruses are likely to be in aggregated states (Figure S2 for details).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This labelling approach for enveloped viruses has been applied by multiple groups including us. [11,12,15,39,41] We characterized the labelled viruses upon fluorescence imaging with wide-field illumination and compared the signal intensity using a control system (liposomes labelled with DiI). The particle intensity analysis reveals that < 20 % of the labelled viruses are likely to be in aggregated states (Figure S2 for details).…”
Section: Resultsmentioning
confidence: 99%
“…The purified virus sample was then genome‐inactivated with UV treatment for performing imaging experiments with a relatively lower biosafety requirement. Recently, we have implemented this UV‐inactivation approach (also by other groups [40] ) to examine the binding of SARS‐CoV‐2 to supported lipid bilayers and have shown that controlled UV exposure affects the viral genome without perturbing the intact viral structure [39] (data in Figures S1A–C). The S protein remains functional for antibody binding as detected upon immunoblotting (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even pathogens utilize gangliosides as membrane receptors or attachment factors for their cellular attachment and entry. For example, GM1 is a cellular receptor of cholera toxin and E. coli , tetanus, and botulinum neurotoxins bind to GT1b ganglioside, viruses like influenza A virus, Sendai virus, and polyomaviruses bind to membrane gangliosides, ,, and recently, we showed that gangliosides are attachment factors of SARS-CoV-2 …”
Section: Introductionmentioning
confidence: 99%